Family - Johannes Huinink (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Family policy gained considerable relevance which is reflected by the current public attention to family issues. In regard to many recommendations of the KVI in 2001 improvements can be reported which family research profited from in a considerable way. However, pertaining to quality and content progress in data provision since the beginning of the 21st century was limited. Particularly, the availability of longitudinal data to study social and family related processes on different levels and regarding different dimensions of family development has to be extended. Data are needed not only to describe family change in an adequate way but also to model the structural and non-structural determinants and `outcomes' of couples' and family dynamics or family relationships over time – both retrospectively and prospectively. Therefore, additionally to an improved family related report system provided by the official statistics prospective panel studies collecting longitudinal (socio-)structural and non-structural information on the dynamics of individuals' living arrangements over time are urgently needed.
Keywords: 330; family research; longitudinal data; family dynamics